(untitled) (Indian Journal of Public Health Research & Development, 2025)
Background: Chronic pain patients have been reported to complain about poor sleep quality and associated depression. Depressive mood and pain severity are the most frequently encountered predictors. The study was done to examine the impacts of chronic pain on depression and poor sleep quality dimensions. Materials & Methods:The study was a prospective, comparative, observational outcomes research study.The study was conducted at two dedicated pain clinics - one government and one private Pain Clinic in Kolkata; and one public routine health care facility.In the present study chronic pain related quality of life in health (patient’s mental status and pain disability) was assessed at baseline, during follow-up visit and end of the study.Association of depression, anxiety and sleep disturbances among chronic pain patients were also assessed. Results: Moderately severe depression was more prevalent in group 2 (15%), whereas moderate depression was more common in group 3 (40%) as compared to other groups. Severe depression was mainly absent in the majority of our study population except group 2 where 5% participants were assessed having severe depression. Sleep disturbances were more prevalent in group 3 patients (7.475 ± 2.0247) initially as compared to other groups. There was significant improvement in quality of sleep among all three groups (p<0.0001) after 6 months of treatment with most prominent improvement in group 3 patients (3.5 ± 1.7319).Conclusion:Chronic pain patients suffer from poor sleep quality—a function of depressed mood rather than pain intensity, duration, or anxiety. Future longitudinal studies with larger sample sizes are needed to confirm the mediating effect of poor sleep quality.